A Philosophical Introduction of Islamic Political System and Social Behavior - Abdulaziz Omar A. Jughaiman (European Scientific Journal, ESJ, 2019)
This paper focuses on exploring Islamic social behavior and Islamic political system nature as a religion from a scientific and philosophical perspective and the most important Islamic aims in politics and society. It also aims to explore the phenomenon, true concepts, and the concepts of its ideology in addition to suggesting various definitions. This paper used a logical analysis method, philosophical interpretations, and verses of the Holy Quran without subjecting it to a specific interpretation. It also used measurement and deduction method, and it compares different political systems and different social structures, in Islamic and non-Islamic country, based on common factors and special Islamic factors. This present paper shows that Muslim community behavior is subjected to religious orientation and the state law. This paper found that Islam calls for peace and accepts modern political concepts. Islamic country should accept the concept of party rather than the concept of group. Also, Islam calls for a social behavior that respects privacy by forbidding spying and criticizing an individual within the scope of his personal life. This paper found that entry into Islam is optional, while getting out of Islam is not optional. This paper also diagnoses the civilization clash and how to avoid it. Therefore, this paper hereby suggests the explanations and definitions of many important phenomenon and concepts, which would contribute to a better understanding of many phenomena in the religion, ethic, law, society, and politics for better decision-making.